2022
DOI: 10.3389/falgy.2022.851993
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the Microbiome, Environment, and Genetics to Mucosal Type 2 Immunity and Anaphylaxis in a Murine Food Allergy Model

Abstract: There is heterogeneity inherent in the immune responses of individual mice in murine models of food allergy, including anaphylaxis, similar to the clinical heterogeneity observed in humans with food allergies to a defined food. One major driver of this heterogeneity may be differences in the microbiome between sensitized individuals. Our laboratory and others have reported that disruption of the microbiome (dysbiosis) by broad spectrum antibiotics and/or yeast colonization can alter systemic immunity and favor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 90 publications
0
2
0
Order By: Relevance
“…With respect to the variables mentioned above, although we have not observed any differences between male or female mice or mice obtained from different vendors, we have not yet conducted a detailed analysis probing these and other factors in our model. In particular, the effects of the gut microbiome and mouse environment need to be further investigated, as suggested by a recent comprehensive study, which demonstrated that the gut microbiome, mouse facility, and mouse genetics all play a critical role in shaping the heterogeneity of MC responses during food allergy ( 64 ). Interestingly, these investigators also observed a direct correlation between increased IL-10 levels and mice developing anaphylaxis, suggesting that the gut microbiome may also modulate the effects of IL-10 on MC activation.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to the variables mentioned above, although we have not observed any differences between male or female mice or mice obtained from different vendors, we have not yet conducted a detailed analysis probing these and other factors in our model. In particular, the effects of the gut microbiome and mouse environment need to be further investigated, as suggested by a recent comprehensive study, which demonstrated that the gut microbiome, mouse facility, and mouse genetics all play a critical role in shaping the heterogeneity of MC responses during food allergy ( 64 ). Interestingly, these investigators also observed a direct correlation between increased IL-10 levels and mice developing anaphylaxis, suggesting that the gut microbiome may also modulate the effects of IL-10 on MC activation.…”
Section: Discussionmentioning
confidence: 99%
“…8A). Stark et al [40] found a disruption of the microbiota and a reduction in Lachnoclostridium in allergic BALB/c mice. But more importantly, we found higher levels of Enterococcus faecium in the treatment group relative to the MAd and MOVA groups.…”
Section: Oral Administration Of B Coagulans Modulated Intestinal Flor...mentioning
confidence: 99%